Influence of Gender and Gender Role Attitudes on Japanese Employees’ Evaluations of Female Managers: Evidence from a Nationwide Survey of Full-Time Workers - Muto, Mami (Advances in Social Sciences Research Journal, 2025)
Women are increasingly expected to play active roles in Japanese society. However, they remain underrepresented in political leadership and corporate decision-making positions, and gender inequality persists. This study examined whether individuals’ gender role attitudes influence their psychological acceptance of women managers and whether this evaluation differs by the evaluator’s gender. The study used an online research panel to collect data from 1,102 full-time Japanese employees (552 men and 550 women, age range 20 to 61 years, Mean age = 43.89, SD = 12.53) and applied a 3-factor between-subjects design: gender role attitude (traditional vs. egalitarian) × manager gender (male vs. female) × participant gender (male vs. female). Results indicated that the three-way interaction was non-significant. However, we observed two significant two-way interactions between a manager’s gender and gender role attitude and between a manager’s and a participant’s gender. Male and female participants with egalitarian gender role attitudes evaluated male managers more favorably than female managers. However, participants with egalitarian attitudes were more accepting of male or female managers than those with traditional attitudes. These findings reflect real-world workplace experiences where people observe a limited number of female role models as managers and heavy burdens placed on women in such roles, including professional responsibilities, domestic work, childcare, and elder care. Additionally, younger participants evaluated managers more negatively, regardless of gender. These generational differences are discussed within the context of current economic conditions in Japan and the younger generation’s employment and living environments.